Volkova O. M., Gurin A. Y. Metaphorical basis of Ukrainian folk riddles - Volkova O. M.; Gurin A. Y. (Philological Treatises, 2020)
In this article types of metaphoric transfer depending on the compared criteria of objects in Ukrainian riddles are under analysis. The basis of understanding the essence of the riddle is in creating a metaphoric equivalent, instead of a real object.